ROS-generating alginate-coated gold nanorods as biocompatible nanosonosensitisers for effective sonodynamic therapy of cancer - Yean Leng Loke; Adilet Beishenaliev; Pei-Wen Wang; Chung-Yin Lin; Chia-Yu Chang; Yiing Yee Foo; Farid Nazer Faruqu; Bey Fen Leo; Misni Misran; Lip Yong Chung; Dar-Bin Shieh; Lik Voon Kiew; et al. (Ultrasonics Sonochemistry, 2023)
Sonodynamic therapy (SDT) emerges as a promising non-invasive alternative for eradicating malignant tumours. However, its therapeutic efficacy remains limited due to the lack of sonosensitisers with high potency and biosafety. Previously, gold nanorods (AuNRs) have been extensively studied for their applications in photodynamic or photothermal cancer therapy, but their sonosensitising properties are largely unexplored. Here, we reported the applicability of alginate-coated AuNRs (AuNRsALG) with improved biocompatibility profiles as promising nanosonosensitisers for SDT for the first time. AuNRsALG were found stable under ultrasound irradiation (1.0 W/cm2, 5 min) and maintained structural integrity for 3 cycles of irradiation. The exposure of the AuNRsALG to ultrasound irradiation (1.0 W/cm2, 5 min) was shown to enhance the cavitation effect significantly and generate a 3 to 8-fold higher amount of singlet oxygen (1O2) than other reported commercial titanium dioxide nanosonosensitisers. AuNRsALG exerted dose-dependent sonotoxicity on human MDA-MB-231 breast cancer cells in vitro, with ∼ 81% cancer cell killing efficacy at a sub-nanomolar level (IC50 was 0.68 nM) predominantly through apoptosis. The protein expression analysis showed significant DNA damage and downregulation of anti-apoptotic Bcl-2, suggesting AuNRsALG induced cell death through the mitochondrial pathway. The addition of mannitol, a reactive oxygen species (ROS) scavenger, inhibited cancer-killing effect of AuNRsALG-mediated SDT, further verifying that the sonotoxicity of AuNRsALG is driven by the production of ROS. Overall, these results highlight the potential application of AuNRsALG as an effective nanosonosensitising agent in clinical settings.